LINGUISTICS VARIETIES : REGISTER IN ENGLISH FANFICTION KPOP “Miss Perfect Idol” - Reni Mulyani; Lilis Suryani (PROJECT (Professional Journal of English Education), 2019)
English fanfiction kpop was the stories who created by fans’ to their idol by their imagination and used English in created the stories the reason was because kpopers / readers whole the world can read the stoeries and benefit for the author can improved their English skill especially in writing and vocabulary. The objectives of this study were to describe the linguistics form and the meaning of register used in English fanfiction kpop “Miss Perfect Idol” at www.asianfanfics.com website. The method used in this study was descriptive qualitative method. The data obtained from www.asianfanfics.com on 24th February 2018 . The researchers found out the linguistic forms in English fanfiction kpop “Miss Perfect Idol” there were noun (twenty five data of noun), adjective (six data of adjective) , verb (five data of verb), interjection (two data of interjection), adverb of place (one data of adverb of place). In the meaning of register the reseachers found the high frequency data of register meaning that was contextual meaning, the data consist of 20 contextual meaning (51.3%) and 19 lexical meaning (48.7%). The contextual meaning more frequently appeared because there were a lot of new vocabularies created by kpopers and the author of fanfic and the vocabularies used in fanfiction.